Optimasi Ekstraksi Sisik Naga (Drymoglossum Piloselloides) Tumbuhan Epifit Gambut Kalimantan Menggunakan Central Composite Design untuk Aktivitas Antioksidan. - Arsana, Muafa Purwa; Monita, Dita; Rahman, Sudarman; Riana, Shesanti Citra; Febrianto, Yahya; Suprayogi, Thatit; Alfanaar, Rokiy; Fatiqin, Awalul (Jurnal Farmasi & Sains Indonesia, 2024)
Dragon scale (Drymoglossum piloselloides) leaf is a plant that contains secondary metabolites with antioxidant potential. This plant is known for its easy to grow nature and has a wide habitat distribution. The extraction method using acetone solvent has been proven effective in extracting secondary metabolites from this plant. To improve the extraction efficiency, this study used an optimization approach using the Central Composite Design (CCD) method. CCD involves three main factors in extraction experiments, namely solvent concentration, extraction time, and extraction temperature. Experiments were conducted with variations of these factors to find the optimal extraction conditions. The results of CCD method showed that the solvent concentration of 70%, extraction temperature at 52°C, and extraction time of 60 minutes. Statistical analysis showed that the model used was significant, with an F-value of 9.20 and a P-value less than 0.01159, indicating that the factors tested had a significant effect on the extraction results. The results of this study have great potential in maximizing the use of dragon scale leaves as a source of antioxidant secondary metabolites.